Incidental Finding of Isolated Accessory Mitral Valve Tissue in Two Adults - Zhaofen Wang; Fang Du; Hao Zhu; Yuzhe Song; Lijuan Huang; Yi Yan; Peng Chang (Clinical Case Reports)
ABSTRACT Accessory mitral valve tissue is a rare congenital anomaly often linked to the anterior mitral leaflet, diagnosed via echocardiography. It may cause left ventricular outflow tract obstruction, with prognosis depending on obstruction severity and regular monitoring essential in asymptomatic cases.